CT-Guided Microcoil Localization of Small Peripheral Pulmonary Nodules to Direct Video-Assisted Thoracoscopic Resection without the Aid of Intraoperative Fluoroscopy - Huang, Zhen-guo (Korean J Radiol, 2021)
OBJECTIVE: To evaluate the feasibility, safety, and effectiveness of CT-guided microcoil localization of solitary pulmonary nodules (SPNs) for guiding video-assisted thoracoscopic surgery (VATS). MATERIALS AND METHODS: Between June 2016 and October 2019, 454 consecutive patients with 501 SPNs who received CT-guided microcoil localization before VATS in our institution were enrolled. The diameter of the nodules was 0.93 ± 0.49 cm, and the shortest distance from the nodules to the pleura was 1.41 ± 0.95 cm. The distal end of the microcoil was placed less than 1 cm away from the nodule, and the proximal end was placed outside the visceral pleura. VATS was performed under the guidance of implanted microcoils without the aid of intraoperative fluoroscopy. RESULTS: All 501 nodules were marked with microcoils. The time required for microcoil localization was 12.8 ± 5.2 minutes. Microcoil localization-related complications occurred in 179 cases (39.4%). None of the complications required treatment. A total of 463 nodules were successfully resected under the guidance of implanted microcoils. VATS revealed 38 patients with dislocated microcoils, of which 28 underwent wedge resection (21 cases under the guidance of the bleeding points of pleural puncture, 7 cases through palpation), 5 underwent direct lobectomy, and the remaining 5 underwent a conversion to thoracotomy. In 4 cases, a portion of the microcoil remained in the lung parenchyma. CONCLUSION: CT-guided microcoil localization of SPNs is safe and reliable. Marking the nodule and pleura simultaneously with microcoils can effectively guide the resection of SPNs using VATS without the aid of intraoperative fluoroscopy.